Built to succeed: sustainable learning environment at UC Merced Library. Issue 2 (14th March 2017) - Li, Haipeng
Abstract : Purpose: The purpose of this paper is to explore the sustainable learning environment at UC Merced Library. Design/methodology/approach: Case study. Findings: The Library is built to support active and constructive learning through its sustainable design as an open, collaborative, and welcoming learning environment and it has become a sustainable environment that supports sustainable learning for the future. Originality/value: As the first new research university campus of the twenty-first Century in America, University of California, Merced (UC Merced), from its very beginning, has embraced principles of a green campus from ground up – sustainable economic, social, and environmental systems that preserve the ability of future generations to meet their own needs.